2004
DOI: 10.1289/ehp.6912
|View full text |Cite
|
Sign up to set email alerts
|

An Unrecognized Source of PCB Contamination in Schools and Other Buildings

Abstract: An investigation of 24 buildings in the Greater Boston Area revealed that one-third (8 of 24) contained caulking materials with polychlorinated biphenyl (PCB) content exceeding 50 ppm by weight, which is the U.S. Environmental Protection Agency (U.S. EPA) specified limit above which this material is considered to be PCB bulk product waste. These buildings included schools and other public buildings. In a university building where similar levels of PCB were found in caulking material, PCB levels in indoor air r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
147
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(150 citation statements)
references
References 6 publications
1
147
2
Order By: Relevance
“…Recently, investigators have reported high concentrations of PCBs in dust associated with certain construction materials, such as caulking (Herrick et al, 2004) and wood floor finish , as well as with a PCB-contaminated fluorescent light ballast (Seidel et al, 1996) and a PCBcontaminated carpet pad (Franzblau et al, 2009). The prevalence of these particular PCB sources in residences is unknown; however, they are unlikely to be relevant in most homes.…”
Section: Determinants Of Pcb Levels In Residential Dustmentioning
confidence: 99%
“…Recently, investigators have reported high concentrations of PCBs in dust associated with certain construction materials, such as caulking (Herrick et al, 2004) and wood floor finish , as well as with a PCB-contaminated fluorescent light ballast (Seidel et al, 1996) and a PCBcontaminated carpet pad (Franzblau et al, 2009). The prevalence of these particular PCB sources in residences is unknown; however, they are unlikely to be relevant in most homes.…”
Section: Determinants Of Pcb Levels In Residential Dustmentioning
confidence: 99%
“…However, exposure may also occur through dermal contact (soil and house dust) and inhalation (indoor air in residential buildings and workplaces, as well as outdoor air). For example, in the 1960s-1970s PCBs were used in sealants for commercial building construction, and high levels of PCBs have been found to remain in the caulking of some public buildings which may lead to contamination of indoor air and dust (Herrick et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…PCBs have been measured in indoor air in several studies (Vorhees et al, 1997;Vorhees et al, 1999;Herrick et al, 2004;Colt et al, 2005;Franzblau et al, 2009;Harrad et al, 2009). In the USA it was reported that indoor air concentrations of PCBs were 5-300 times greater than those in outdoor air (Wallace et al, 1996), and that concentrations were higher in older buildings.…”
Section: (A) North Americamentioning
confidence: 99%